A mixed method evaluation of an integrated course in improving critical thinking and creative self-efficacy among nursing students. (November 2021) - Liu, Ting; Yu, Xuan; Liu, Man; Wang, Min; Zhu, Xiuli; Yang, Xiuling
Abstract: Background: Critical thinking and creative self-efficacy are important for nursing students to provide quality patient care in an increasingly complex healthcare environment. Educators play a role in cultivation of corresponding skills in university settings. Objectives: To develop an integrated course addressing the core elements of critical and creative thinking in one nursing program and evaluate its impacts on students' creative thinking disposition and creative self-efficacy. Design: A mixed methods study using a quasi-experimental comparative design and a descriptive qualitative analysis of students' reflective journals. Settings: A university pre-registration nursing program in Mainland China. Participants: A total of 68 second-year nursing students. Methods: The course was developed as a sixteen-week two-hour program. It was comprised of 7 modules covering the concepts, pathways, and skills of critical and creative thinking, related tools and the application in nursing. Quantitative and qualitative data were collected before and after the course to obtain a comprehensive understanding of the course effects. Quantitative outcomes included students' level of creative thinking disposition and creative self-efficacy measured by specific scales; qualitative outcomes were obtained through student journals. Paired sample t- tests were performed to compare the changes between pre- and post-tests. Thematic analysis was applied to analyze the qualitative data from students' reflective journals. Results: Quantitative data showed that except in the self-confidence and originality dimensions, students' scores of overall creative thinking disposition, creative self-efficacy, and other dimensions were significantly improved after the 16-week course. Qualitative data revealed that students' understanding and practice of creative thinking and creative self-efficacy were deeply shaped by the social, cultural, and educational contexts. Conclusions: This study demonstrated that an integrated course of critical and creative thinking exerted distinct impacts on increased levels of creative thinking dispositions and creative self-efficacy among second-year nursing students in China. Students favored and benefited from the course in both personal and professional domains. Highlights: Students favored an integrated course with elements of critical thinking and creative thinking. Students' overall critical thinking disposition was significantly improved after the course. Students' overall creative self-efficacy was significantly enhanced after the course. No significant changes were found in dimensions of self-confidence and originality. A mixed method evaluation indicated the sociocultural influence on thinking.